Helicobacter Pylori Infection of Lingual Dorsum: Risk of Gastric Infection Helicobacter Pylori - Muiños, Antonio Luis (2021)
The role of Helicobacter pylori in the oral cavity has been researched/studied by our study group for the last 28 years. At that time, there wasn’t a clinical entity that included Burning, Lingual Papillary Hypertrophy and Halitosis (BHH) together. However, the patients who presented this condition did not find an effective response to their demand. In some cases, a therapeutic diagnosis of Chronic Candidiasis was made in relation to Lingual Papillary Hypertrophy and they were referred to Periodontics Services for their Chronic Halitosis for evaluation and treatment. Many of these patients did not resolve their clinical symptoms, in their subsequent check-ups. The burning of the mouth was usually diagnosed as Burning Mouth Syndrome. A considerable percentage (60%) of these patients reported suffering from chronic gastric discomfort without receiving treatment, because when they consulted with the physician or with the gastroenterologist, their symptoms were associated with stress.